2020
DOI: 10.1007/s00338-020-01910-0
|View full text |Cite
|
Sign up to set email alerts
|

Photophysiology of a mesophotic coral 3 years after transplantation to a shallow environment

Abstract: With shallow coral reefs suffering from an ongoing rapid decline in many regions of the world, the interest in studies on mesophotic coral ecosystems (30-150 m) is growing rapidly. While most photoacclimation responses in corals were documented within the upper 30 m of reefs, in the present study we transplanted fragments of a strictly mesophotic species from the Red Sea, Euphyllia paradivisa, from 50 m to 5 m for a period of 3 years. Following the retrieval of the corals, their physiological and photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…In our experiment, the transplanted corals increased the number of Symbiodiniaceae cells (Figure 1F), while the chlorophyll a concentrations per total protein decreased nearly to the same levels of shallow colonies (Figure 1H). Transplantation experiments that were done on S. pistillata and other species in a natural environment (Winters et al, 2009;Cohen and Dubinsky, 2015;Ben-Zvi et al, 2020) observed the same trend we see here, probably as a result of the higher plankton availability and nutrient sources in the shallow reef. An increase in zooplankton indeed leads to higher symbiont cells density in corals (Muscatine et al, 1989).…”
Section: Discussionsupporting
confidence: 82%
“…In our experiment, the transplanted corals increased the number of Symbiodiniaceae cells (Figure 1F), while the chlorophyll a concentrations per total protein decreased nearly to the same levels of shallow colonies (Figure 1H). Transplantation experiments that were done on S. pistillata and other species in a natural environment (Winters et al, 2009;Cohen and Dubinsky, 2015;Ben-Zvi et al, 2020) observed the same trend we see here, probably as a result of the higher plankton availability and nutrient sources in the shallow reef. An increase in zooplankton indeed leads to higher symbiont cells density in corals (Muscatine et al, 1989).…”
Section: Discussionsupporting
confidence: 82%
“…Reef complexity creates distinct microenvironments 48 such as the low light conditions under the overhangs from which O. patagonica resides at our shallow collection site. At both depths, colony physiology was more typical of mesophotic corals 6 , 24 , 49 and had relatively different physiology compared to a temperate congener, O. arbuscula 50 or the symbiotic stony coral C. caespitosa 23 , 51 such as high chlorophyll concentration (3.9 ± 0.38 pg chlorophyll cell −1 , an average of all corals combined), high photosynthetic efficiency (0.61 ± 0.002), low saturation irradiance (100.35 ± µmol m −2 s −1 ), and low calcification rates (0.402 ± 0.09 µmol CaCO 3 cm −2 h −1 ). Overall, such physiology permits O. patagonica’s growth in low light environments and may in part explain the ability of this species to proliferate at mesophotic depths.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration and photosynthesis data from mesophotic corals are very limited and there is currently no agreed protocol for performing these measurements. Although Mass et al (2010) provided evidence for the chromatic dependence of photosynthetic performance on the light provided during measurements, ex-situ measurements on mesophotic corals are still commonly performed under white light (Cooper et al, 2011;Ben-Zvi et al, 2020). Since corals are known to photoacclimatize to their natural light conditions, mesophotic corals are most likely acclimatize to blue light, as this is the prominent wavelength at depths of 30-150 m (Kahng et al, 2019).…”
Section: Speciesmentioning
confidence: 99%
“…These changes, among others, potentially assist corals in maintaining a successful symbiosis with Symbiodiniaceae. Accordingly, deeper corals will usually present a higher maximal quantum yield of photosystem II (Einbinder et al, 2016;Ben-Zvi et al, 2020), a lower Symbiodiniaceae density accompanied by higher chlorophyll concentration within algal cells (Mass et al, 2007), and a reduced capacity to manage excess light (Einbinder et al, 2016;Ben-Zvi et al, 2020). Additionally, mesophotic corals may rely more on heterotrophy rather than autotrophy as their main strategy for acquiring energy (Mass et al, 2007;Lesser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%